FILLING THE EDUCATIONAL SPACE OF PERSONAL STUDENT PERSONALITY DEVELOPMENT DURING THE PERIOD OF ADAPTATION TO SCHOOL LIFE (SYSTEM OF DEVELOPMENTAL DEVELOPMENT) - Kysilova-Bila, V.P.; Frankiv, I.I. (Pedagogy of Higher and Secondary Education, 2022)
The article describes process of creation and filling the subsystem of educational space such as "teacher-child-parents" in the adaptionall period of child's entrance to a school life of system of developing training.